On the gustiness of wind and occurrence of gusts at Vishakhapatnam - Agarwala, K.S. (MAUSAM, 1951)
The paper summarises the results of a study of the gustiness of wind and of the occurrence of gusts at Vishakhapatnam, based on the analysis of 3 years' records of the Dines Pressure Tube Anemograph with its head above ground. Tables showing the diurnal variation of gustiness for the twelve months of the year are given and briefly discussed. Frequencies of the time of occurrence, speeds and directions of the gusts ate also given and their chief features arc described. The highest gusts recorded in each one of the three years ate also discussed.